Cases in comparative politics - O'Neil, Patrick H (New York: Library of Congress Cataloging, 2006)
Contents: United Kingdom. United States. Francia. Japón. Rusia. China. India. Iran. Mexico. Brazil. Africa del Sur. Nigeria
Keywords: Comparative Government - Case Studies